2014
DOI: 10.1038/nrcardio.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of heart failure with preserved ejection fraction

Abstract: Approximately half of all patients with heart failure have preserved ejection fraction (HFpEF) and, as life expectancies continue to increase in western societies, the prevalence of HFpEF will continue to grow. In contrast to heart failure with reduced ejection fraction (HFrEF), no treatment has been proven in pivotal clinical trials to be effective for HFpEF, largely because of the pathophysiological heterogeneity that exists within the broad spectrum of HFpEF. This syndrome was historically considered to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
537
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(565 citation statements)
references
References 138 publications
(225 reference statements)
14
537
1
13
Order By: Relevance
“…Furthermore, a significant correlation between serum BNP level and CFR was also observed in this study. A previous study showed that BNP level is a prognostic marker for HFpEF 7. Our finding suggests that impairment of CFR might predict future cardiovascular events in HFpEF patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, a significant correlation between serum BNP level and CFR was also observed in this study. A previous study showed that BNP level is a prognostic marker for HFpEF 7. Our finding suggests that impairment of CFR might predict future cardiovascular events in HFpEF patients.…”
Section: Discussionsupporting
confidence: 66%
“…Outcomes for patients with HFpEF are poor and are similar to those of heart failure (HF) patients with reduced ejection fraction (EF) 1, 4. However, an effective treatment of HFpEF has not been identified because the precise pathophysiological mechanisms of HFpEF have not been fully elucidated 7. The pathophysiology of HFpEF is complex and multifactorial and includes diastolic dysfunction,8 myocardial ischemia, cardiomyocyte hypertrophy, cardiac inflammation,9 and endothelial dysfunction 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…This is independent of the use of negative chronotropic medication (such as betablockers). The phenomenon is probably an expression of either local desensitisation of beta-adrenergic receptors in the sinus node or global autonomic dysfunction (7,19).…”
Section: Chronotropy and Atrial Fibrillationmentioning
confidence: 99%
“…Peripheral vascular function is compromised in HFpEF patients (7). Microvascular dysfunction affects the small vessels both in the coronary circulatory system and in peripheral organs.…”
Section: Vascular Dysfunction and Ventricular Vascular Couplingmentioning
confidence: 99%
See 1 more Smart Citation